x+3=-8-5x

Simple and best practice solution for x+3=-8-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+3=-8-5x equation:



x+3=-8-5x
We move all terms to the left:
x+3-(-8-5x)=0
We add all the numbers together, and all the variables
x-(-5x-8)+3=0
We get rid of parentheses
x+5x+8+3=0
We add all the numbers together, and all the variables
6x+11=0
We move all terms containing x to the left, all other terms to the right
6x=-11
x=-11/6
x=-1+5/6

See similar equations:

| -16x—8x+17x—12=-15 | | 15.75+0.05h=16.53-0.13 | | 4(b+3)=52 | | 15.75+0.05h+3h=16.53-0.13 | | 3/4c+4=-20 | | (-0.5m)-0.75=2.15 | | 7–4b=–9.b= | | X^4+5x^2+2=0 | | 7k=195 | | 2b+1=17 | | x51+80+60=180 | | 31=6g | | 3x-4x-9=-6 | | 13x+9=32 | | 14x+3-3x+7=4x-9+3x-21 | | 31=6q | | -3x+6x+15=5x+2x-x | | 3(p-9)=-3 | | 15x-13x-2=20 | | 6m+3=2m+7 | | X15-20=y5 | | 6x-(-8)=-2-(-2x) | | 5x-7=3x19 | | 2s+5=15s+ | | 4(b-4)-10=2(b-3) | | 5b=89 | | 9p+7=11 | | 3b+4=10b= | | 4=3+m | | 5x-3x+5=3x+2x-1 | | 1/2x−5=12 | | 9p=11=7 |

Equations solver categories